Bibliometric Analysis of Gastronomic Tourism - Loso Judijanto (West Science Social and Humanities Studies, 2025)
This study conducts a bibliometric analysis of gastronomic tourism research to understand its intellectual structure, key contributors, and emerging themes. Through the examination of publications indexed in Scopus, this study identifies the prominent trends, motivations, and developments within the field of gastronomic tourism. The findings reveal significant thematic clusters related to sustainability, local food, food heritage, and tourism marketing. As globalization and digitalization continue to shape the tourism landscape, this study underscores the growing importance of integrating food heritage into tourism strategies and the role of online platforms in promoting culinary tourism. The research highlights the intersection of food and cultural identity, suggesting that gastronomic tourism is an essential driver for regional development and sustainable tourism practices. Despite the advances in the field, there are notable gaps, including the need for a broader understanding of culinary tourism beyond Europe and East Asia, and more interdisciplinary research integrating gastronomic tourism with other niche sectors.